Remembering Friends as Not So Friendly in Competitive and Bargaining Social Interactions. (16th May 2017) - Danziger, Shai; Disatnik, David; Shani, Yaniv
Abstract: From children's schoolyard play to executives' boardroom negotiations, competitive and bargaining interactions are common to everyday life. Sometimes, the interacting parties are socially close and sometimes not. In this research, we examine how friendship influences memory for actions in such interactions. Dyads consisting of either friends or strangers played a competitive card game (Study 1) or the ultimatum game (Studies 2 and 4) and then recalled the interaction. We find that participants remembered friends' play as more competitive (Study 1) and less generous (Studies 2 and 4) than strangers' play, even when friends' actual play was more generous than that of strangers (Studies 2 and 4). Friendship did not affect recall for one's own play. In a workplace setting, Study 3 reveals people expect more of work colleagues who are friends than of work colleagues who are acquaintances. Study 4 tests our complete model and shows that people expect more of friends than of strangers and that this difference in expectations explains the less favorable memory for friend's actions. Our findings are consistent with a negative disconfirmation account whereby people expect their friends to be less competitive and more generous, and when these expectations are violated, people remember friends' actions more negatively than they actually were. Much research shows positive effects of friendship norms on actual behavior. We demonstrate a negative effect on people's memory of friends' behavior in competitive and bargaining social interactions. Copyright © 2017 John Wiley & Sons, Ltd.